ANALYSIS OF PATHOGENIC FUNGAL DIVERSITY ON OIL PALM (Elaeis guineensis Jacq.) LEAVES EXHIBITING DISEASE SYMPTOMS - Nurliana Nurliana; Satria Pratama (Universitas Medan Area, 2026)
Oil palm (Elaeis guineensis Jacq.) is a strategic plantation commodity in Indonesia, but its productivity is often affected by diseases, particularly pathogenic fungal infections that reduce the photosynthetic area of leaves. This study aimed to identify and characterize the morphology of pathogenic fungi causing oil palm leaf diseases at Sei Merah Plantation, PT PP London Sumatra Tbk. A qualitative descriptive approach was employed using purposive sampling of 20 symptomatic leaves from 10 oil palm trees aged 5–8 years. Fungal isolation was conducted on Potato Dextrose Agar (PDA), followed by macroscopic and microscopic identification using lactophenol cotton blue staining. Infected leaves showed brown to blackish necrotic spots, chlorosis, and severe blight resulting in leaf tissue desiccation. Eleven isolates were identified into three genera, with Fusarium sp. and Curvularia sp. showing the highest equal proportions (36.36% each), followed by Rhizoctonia solani (27.27%). Colony growth rates ranged from 8.3–12.7 mm/day, with Curvularia sp. growing fastest (12.4 mm/day). The Shannon–Wiener index (H′ = 1.09), evenness (E = 0.99), and Simpson dominance index (C = 0.34) indicated a relatively balanced pathogen community without absolute dominance. These findings highlight the need for integrated disease management based on accurate morphological identification.